Performance evaluation of policies on banned agrochemicals among marketers in Nigeria - Fakayode S.B.; Agunbiade B.O.; Omolehin R.A.; Olatawura O.O.; Olowogbon T.S. (Journal of Tropical Agriculture, 2025)
Agrochemical use is known to have many challenges that need to be properly addressed in order to realize the desirable results. The different players in the agrochemical value chain must contribute significantly to ensure the safe production, distribution, handling and use of these substances towards mitigating the adverse impacts. The current study evaluates the effectiveness of policies on banned agrochemicals among the market chain actors in Nigeria. A total of 50 marketers of agrochemicals were randomly selected from two Local Government areas in Ekiti state, Nigeria for this study. The primary data was collected with the aid of questionnaire and subjected to descriptive analysis such as frequency counts, percentages, weighted mean and standard deviation. Results show that only 5 out of the 30 listed banned agrochemicals could be identified by more than 50.0% of the marketers. The level of compliance with the ban on agrochemicals showed that more than 50% of marketers were still into the sales of 30 to 40% of these banned chemicals with the attendant negative implications both to man and the environment. The study recommends adequate enlightenment by extension agents on banned agrochemicals to the suppliers and marketers in Nigeria